2018
DOI: 10.3758/s13415-018-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the neural underpinnings of social and monetary incentive processing during adolescence

Abstract: The brain's reward system undergoes major changes during adolescence, and an increased reactivity to social and nonsocial incentives has been described as a typical feature during this transitional period. Little is known whether there are sex differences in the brain's responsiveness to social or monetary incentives during adolescence. The aim of this event-related potential (ERP) study was to compare the neurophysiological underpinnings of monetary and social incentive processing in adolescent boys versus gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 83 publications
4
24
0
Order By: Relevance
“…Further, only girls demonstrated FRN to monetary punishment in relation to a reward sensitivity trait. In another EEG study of an incentive delay task, boys as compared to girls showed reduced stimulus-preceding negativity when anticipating punishment and greater feedback P3 to monetary than social reward (33). These findings are consistent with a literature of higher female sensitivity to loss, punishment or other negative feedback (27,34,35).…”
Section: Sex Differences In Reward and Punishment Processingsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, only girls demonstrated FRN to monetary punishment in relation to a reward sensitivity trait. In another EEG study of an incentive delay task, boys as compared to girls showed reduced stimulus-preceding negativity when anticipating punishment and greater feedback P3 to monetary than social reward (33). These findings are consistent with a literature of higher female sensitivity to loss, punishment or other negative feedback (27,34,35).…”
Section: Sex Differences In Reward and Punishment Processingsupporting
confidence: 86%
“…Thus, these findings suggest greater male sensitivity to monetary reward, in accord with the literature. For instance, an ERP study in adolescents reported higher feedback P3 amplitude in boys, as compared to girls, in response to monetary rewards (33). Another study reported a preferential response of the OFC to attractive vs. unattractive faces in men but not in women (66).…”
Section: Sex Differences In Response To Feedback and Reward Sensitivitymentioning
confidence: 99%
“…Likewise, electroencephalographic evidence has shown that social and monetary incentive cues evoke differential event-related potential patterns at both early and late temporal stages (Flores et al, 2015). Moreover, neural activation induced by social and monetary reward anticipation are differentially modulated by age (Rademacher et al, 2013), sex (Greimel et al, 2018;Spreckelmeyer et al, 2009;Wang et al, 2017), and social proficiency (Gossen et al, 2014). Taken together, recent evidence suggests a hypothesis that social reward anticipation engages a more complex neural circuit than monetary reward anticipation, consisting of not only reward-related regions (e.g., VS) but also social-cognitive related regions (e.g., dmPFC, TPJ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the current findings should be considered as specific to monetary reward, and more studies are needed to address how men and women differ in behavioral and neural sensitivity to other types (e.g., social) of reward ( Spreckelmeyer et al. 2009 ; Greimel et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%